La concepción dogmática del art. 16.3 de la constitución: reflexiones sobre la pervivencia del formalismo en la hermenéutica constitucional - Polo Sabau, José Ramón (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
This paper will examine the implications of the most common understanding of Spanish legal scholars of the proper meaning of article 16.3 of the Spanish Constitution, in the light of contemporary constitutional doctrine. Concluding the discussion of the contents of the above-mentioned article, we find that it stands in conflict with the substantial protection of constitutional values.